PERESEPAN ANTIBIOTIKA DAN OBAT-OBAT PENYAKIT DEGENERATIF BERDASARKAN KAJIAN RESEP DI KABUPATEN JEMBER TAHUN 2006 - , Wiratmo, Drs., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The development of science and technology that is so rapidly since the 20th century and lasted until now It could be direct or indirect effect on population changes, especially the number of elderly increases in the next result of epidemiological transition occurs. This transition is strongly influenced by demographic changes. Similarly, the pattern of disease that occurs will be shifted from infectious diseases towards chronic diseases or degenerative diseases. Study is to examine prescribing of antibiotics and drugs degenerative disease in Jember regency in the year 2006 This research is non-experimental design with non-descriptive analysis, and retrospective, done through the study doctor's prescription, spread in 12 pharmacies selected in Jember regency in the year 2006. The data has been recorded in the form of research and then calculated in accordance with their respective groups, and then analyzed quantitatively in the form of descriptive evaluative presented in table form. The results from the 6062 pages of recipes that are spread in 12 pharmacies selected in Jember regency in the year 2006 recorded the first three main things that is prescribing antibiotics and medications degenerative disease, the second comparison between antibiotic prescribing with medications degenerative diseases in general and its relationship with causative factors, and the third study reviewed prescription of rationality therapy. From the research, it can be concluded that: the kind most widely prescribed antibiotics are betalactam group of 50.32% comprised penicillin 27.12% and sefalosporin 24.20%, spread mainly among pharmacies in urban areas (Kaliwates & Patrang) . Drug degenerative disease is the most widely used class of cardiovascular drug therapy 49.23%, joint pain / gout 39.11%,, all spread out evenly in selected pharmacies, especially in urban areas. From the calculation results obtained 39.73% of antibiotics and 39.74% drugs of degenerative diseases and other drugs by 20.52%. Third review of several prescription was qualitatively found that no rational prescribing among others, prescribing excessive (over-prescribing), prescribing compound / polypharmacy (multiple prescribing) and extravagant prescribing. For polypharmacy (number of sheets of prescription drugs in the molar or number of drugs in one R /) which theoretically according to the standard according to "Drug Interaction Fact 2009" occurred drug related problems (DRP) that is drug interactions.